2006
DOI: 10.1590/s0100-879x2006000800010
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical, clinical and electroneuromyographic correlative study of the neural markers in the neuritic form of leprosy

Abstract: The nerve biopsies of 11 patients with pure neuritic leprosy were submitted to routine diagnostic procedures and immunoperoxidase staining with antibodies against axonal (neurofilament, nerve growth factor receptor (NGFr), and protein gene product (PGP) 9.5) and Schwann cell (myelin basic protein, S-100 protein, and NGFr) markers. Two pairs of non-adjacent histological cross-sections of the peripheral nerve were removed for quantification. All the fascicles of the nerve were examined with a 10X-ocular and 40X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 21 publications
6
25
0
6
Order By: Relevance
“…Moreover, the authors reported lack of neuropeptides in most of leprosy lesions. Reduction of neurofilament and PGP 9.5 immunostaining in nerve biopsies from pure neuritic leprosy was also demonstrated by Antunes et al 30 , as well as its correlation with reduced potential amplitudes in electroneuromyographic evaluation. Our results have shown positive correlation between p75 NTR and PGP 9.5 (r=0.40; p=0.01), indicating the association between Schwann cells and axons in Remak bundles.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, the authors reported lack of neuropeptides in most of leprosy lesions. Reduction of neurofilament and PGP 9.5 immunostaining in nerve biopsies from pure neuritic leprosy was also demonstrated by Antunes et al 30 , as well as its correlation with reduced potential amplitudes in electroneuromyographic evaluation. Our results have shown positive correlation between p75 NTR and PGP 9.5 (r=0.40; p=0.01), indicating the association between Schwann cells and axons in Remak bundles.…”
Section: Discussionsupporting
confidence: 56%
“…Earlier, it was reported that M. leprae has a strong demyelinating effect on infected Schwann cells (Sc) neuron culture [23]. Further, it was also showed by Antunes et al (2006) [24] that M. leprae has direct destructive effect on the integrity of nerve fibers in leprosy patients. However, our findings suggest that anti-MBP antibodies are associated with extent of nerve involvement in leprosy patients.…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, PCR has proven to be a very useful tool in confirming PNL diagnoses (Antunes et al, 2006). In previous studies, mononeuritis and mononeuritis multiplex have been the most common PNL presentations (de Freitas, 2007).…”
Section: Casementioning
confidence: 99%